Post-traumatic impaction of maxillary incisors: diagnosis and treatment - Paoloni, Valeria (CIC Edizioni Internationali, 2013)
AIM: To provide clinicians with useful information for immediate diagnosis and management of impacted maxillary incisors due to trauma. METHODS: We present a case of post-traumatic impaction of a central right maxillary incisor in a young patient. The treatment plan consisted in the interceptive management (surgical and orthodontic), the valuation of the necessary space to move the impacted tooth in the normal position and the biomechanical approach for anchorage, avoiding prosthetic/implants replacement. RESULTS: The therapy of an impacted maxillary incisor due to trauma requires a multidisciplinary approach: orthodontic, surgical, endodontic and periodontal considerations are essential for successful treatment. CONCLUSIONS: Surgical exposure and orthodontic traction is the treatment most often used in case of posttraumatic impacted incisor: this technique in fact can lead to suitable results at the periodontal, occlusal and esthetics levels at an early stage and more definitively than with other treatment options.